Sacramento-San Joaquin Delta Socioecological Monitoring - Alejo Kraus-Polk; Brett Milligan (Environmental Data Initiative, 2020)
This dataset covers observations of human activities and traces collected during monitoring runs to and on Ecorestore project sites. The dataset provides snapshots of activity at the point and time of monitoring, which occurred during daylight hours on weekdays. Locations are approximate as many observations were recorded by reach (between launches and destinations). The goal of the monitoring project was to assemble a composite and comparative picture of human use and activities in the Sacramento-San Joaquin, based on the following typologies: Waterways, Tracts (reclaimed; Farmed, Wildlife-friendly farmed, Subsidence reversal, Managed marsh/duck club (Suisun Marsh, Yolo Bypass), Other), Flooded tracts (Franks Tract, Big Break), Restoration (Tidal wetlands, Floodplain/levee setback/breaching). This dataset was created as part of the experimental prototyping of a socioecological monitoring protocol. This protocol was developed in collaboration with the CDFW fish restoration program to enable the collection of human use and activity data in and around Ecorestore project sites. The human use data was intended to inform understanding of how restoration affected human uses and activities. The idea was to collect data before, during, and after restoration, which would have enabled a modified Before-After-Control-Impact (BACI) test. Not enough data was collected to effectively conduct this test. Geographic coordinates correspond with an approximate location of monitoring sites and rivers reaches within which observations were recorded.